The African-American female body as spectacle in Hurston’s Their Eyes Were Watching God - Loren Lee (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2015)
Saartjie Baartman, also known as the Hottentot Venus, was an enslaved Khoikhoi woman taken from South Africa and put on display throughout Europe during the 19th century because of her prominent sexual features. Even in death, Baartman did not find peace. Her body was displayed publicly in a museum in France until 1976, and finally, her remains were repatriated to South Africa in 2002 following demands by Nelson Mandela for her return. The female body is often used as the representation of ideas (justice, liberty, abundance). The Hottentot Venus was once a physical representation of the eroticization and manipulation of the black female, but now, she passes into abstraction and becomes yet another metaphorical receptacle of power and ideas. However in Their Eyes Were Watching God, Zora Neale Hurston successfully avoids the literary trope of establishing her protagonist, Janie Mae Crawford, simply as the black woman who overcomes racism and sexism. Rather, Hurston initially establishes Janie Mae Crawford as the exhibit of both racial and sexual power. She then systematically removes the factors that withhold agency and selfhood from Janie to create the concept of a woman that exists separate from the pedestal. Janie escapes the spectacle-spectator relationship and gains selfhood by taking absolute ownership of her body.